Molecular Detection and Immunological Characterization of Leishmania donovani in patients in Wasit province, Iraq - Hraija, Baraa Abdulsalam (American Journal of Biology and Natural Sciences, 2025)
Visceral leishmaniasis is a protozoan parasitic disease of vector-borne transmission with a notable increasing in global incidence and spreading to novel geographic areas. In Iraq, molecular data concerned visceral leishmaniasis remain limited and need to support. Molecular surveying of Leishmania donovani in clinically asymptomatic adults, sequencing and phylogenetic analysis of study isolates, with estimation the levels of some immune markers including IL-1β, IL-10, IFN-γ, and TNF-α. An overall 285 rural adults of 10-70 years age-old and both sexes were selected to sampling of venous blood that divided equally into EDTA-anticoagulant tube for molecular testing by conventional PCR, and free-anticoagulant tube that centrifuged to obtain sera for immunology by quantitative ELISA. The positive L. donovani isolates were sequenced and analysed phylogenetically using the MEGA-11 software and NCBI-Viewer. Molecular findings of PCR assay reported that 4.21% of study population was positively infected with L. donovani. In comparison with the global NCBI-BLAST L. donovani isolates / strains, phylogenetic tree analysis, MSA and homology sequence identity for study L. donovani isolates demonstrated the presence of significant identity with the Brazilian L. donovani isolate (GenBank ID: ON934698.1) at a similarity ranged from 98.50-99.94% and mutation / changes ranged from 0.0003-0.001%. Immunologically, the positively infected individuals express a significant reduced IL-1β, but elevated serum levels of IL-10, IFN-γ, and TNF-α. This represents the first molecular study in Wasit province, and the first phylogenetic one in Iraq demonstrating that there was a close-relationship between the study L. donovani isolates and the global NCBI-GenBank isolates, and estimating levels of some immune markers in infected cases. Author suggests the great necessity of additional molecular phylogenetic and immune studies in cases of leishmaniasis.